False witness - Slaughter, Karin, 1971- (William Morrow, an imprint of HarperCollinsPublishers, 2021)
"AN ORDINARY LIFE ... Leigh Collier has worked hard to build what looks like a normal life. She has a good job as a defense attorney, a daughter doing well in school, and even her divorce is relatively civilized-her life is just as unremarkable as she'd always hoped it would be. HIDES A DEVASTATING PAST ... But Leigh's ordinary life masks a childhood which was far from average ... a childhood tarnished by secrets, broken by betrayal, and finally torn apart by a devastating act of violence. BUT NOW THE PAST IS CATCHING UP ... Then a case lands on her desk-defending a wealthy man accused of rape. It's the highest profile case she's ever been given-a case which could transform her career, if she wins. But when she meets the accused, she realizes that it's no coincidence that he's chosen her as his attorney. She knows him. And he knows her. More to the point, he knows what happened twenty years ago, and why Leigh has spent two decades running. AND TIME IS RUNNING OUT. If she can't get him acquitted, she'll lose much more than the case. The only person who can help her is her younger, estranged sister Callie, the last person Leigh would ever want to ask for help. But suddenly she has no choice .."--